Optimization of operational parameters for the treatment of roof-harvested rainwater with biologically synthesised nanosilver coated on sand. Issue 1 (1st July 2021) - Anoob, Farhana; Meera, V.
Abstract: Rainwater is a major source of drinking water in developing countries. Roof-harvested rainwater is generally microbiologically contaminated and thus needs to be treated effectively to meet drinking standards. Filtration of rainwater with sand coated by silver nanoparticles enhances the microbial removal efficiency. In this study, the filtration parameters of treating rainwater with biologically synthesized nanosilver coated sand are optimized. Of the various synthesis methods, the biological method was chosen due to benefits such as cost-effectiveness and its eco-friendly nature. Silver nanoparticles were synthesised using papaya fruit extract and then coated on sand. The synthesized nanosilver coated sand was subjected to characterization methods such as energy dispersive spectroscopy and X-ray diffraction (XRD) analysis. With silver coated sand as control, multiple long duration tests were performed to treat rainwater with nanosilver coated sand to find the optimal values for filtration parameters such as filter bed depth and empty bed contact time (EBCT). The crystallite size of the nanosilver coated sand was found to be 43.8 nm. The optimal values for filter bed depth and EBCT were found to be 12 cm and 15 minutes respectively. The rainwater treated with nanosilver coated sand met drinking water standard IS 10500: 2012 until the media got exhausted. HIGHLIGHTS: Application of nanotechnology in water treatment. Eco-friendly biological synthesis of silver nanoparticles. Filtration of roof harvested rainwater using nanosilver coated sand. Long duration column tests to evaluate bacterial removal efficiency. Optimization of operational parameters (Bed depth & EBCT) of filtration process.